An instrumental analysis of oral monophthongs in Aceh Barat dialect of Acehnese - Tanzir Masykar; Roni Agusmaniza; Nurul Taflihati Masykar; Febri Nurrahmi (EduLite: Journal of English Education, Literature and Culture, 2021)
As among the ten most spoken languages, Acehnese inevitably has many varieties. Many previous studies on Acehnese have been heavily conducted on the northern varieties of Acehnese, leaving other Acehnese varieties unexplored. Pase dialect of Acehnese has been described to have oral and nasal monophthongs and diphthongs, but no studies on Aceh Barat dialect phonetic features of Acehnese have been made. Aceh Barat dialect has also been stigmatized as being rough and vulgar in the previous study. Thus, the current study aims to explore the instrumental analysis of Acehnese oral monophthongs by Aceh Barat speakers. Three male speakers (aged 35-50 years old) speaking only Acehnese as the local language participated in the current study. The ten Acehnese words used to target the ten phonemes were adapted from study. A total of 90 tokens of Acehnese oral vowels production were analyzed using PRAAT version 6.1.29. The oral monophthongs of the Aceh Barat dialect are generally similar to the previous study on the Pase dialect. Exception emerges for the vowel /ʌ/ and /ə/, which seems to be produced differently across the speakers. Both vowels appear to stretch further down the vowel space closer to the back vowels /u/ and / ɔ/, respectively.